2023
DOI: 10.1177/17531934231166343
|View full text |Cite
|
Sign up to set email alerts
|

Results of arthroscopic cancellous bone grafting for treatment of scaphoid nonunion in comparison with open cancellous bone grafting

Abstract: This study primarily aimed to report the outcome of the arthroscopic cancellous bone grafting technique for treating scaphoid nonunion. The secondary aim was to compare the bone union rate and time, and the ability to correct the angulation of the scaphoid, between arthroscopically treated patients ( n = 27), and patients treated with open cancellous bone grafting ( n = 27). Nine surgeons (two in the arthroscopic and seven in the open group) with Level III experience operated on the patients. The pain score, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Indeed, Gvozdenovic and Kongensgaard recently reported that arthroscopic bone grafting leads to more rapid union than open bone grafting in the setting of scaphoid nonunions, by an average of 5.4 weeks (p ¼ 0.033). 17 Standard fixation constructs have inherent drawbacks. Although cheap and widely available, K-wires can be malleable, confer the risk of pin-site infection, and require a prolonged period of immobilization and a secondary operation for hardware removal.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Gvozdenovic and Kongensgaard recently reported that arthroscopic bone grafting leads to more rapid union than open bone grafting in the setting of scaphoid nonunions, by an average of 5.4 weeks (p ¼ 0.033). 17 Standard fixation constructs have inherent drawbacks. Although cheap and widely available, K-wires can be malleable, confer the risk of pin-site infection, and require a prolonged period of immobilization and a secondary operation for hardware removal.…”
Section: Discussionmentioning
confidence: 99%